An Improved and Scalable Synthesis of the Potent SREBP Inhibitor KK-052 via [3+2] Cycloaddition - Kawagoe, Fumihiro; Mototani, Sayuri; Takemoto, Yasushi; Uesugi, Motonari; Kittaka, Atsushi (Synthesis, 2024)
KK-052 is a novel vitamin-D-based selective sterol regulatory element-binding protein (SREBP) suppressor that lacks vitamin D genomic activity mediated through the vitamin D receptor in both in vitro and in vivo settings. In our initial synthetic effort, KK-052 was produced as one of the structural isomers obtained via the Mitsunobu reaction involving a CD-ring allyl alcohol and 5-phenyl-1H-tetrazole. In this work, we present a refined methodology for enhancing the selective synthesis of KK-052 through a [3+2] cycloaddition between a CD-ring benzimidoyl chloride and sodium azide, a technique that proved amenable to gram-scale production. Additionally, this synthetic method permitted the production of a more potent m-methyl analogue of KK-052.
Keywords: SREBP; vitamin D3; KK-052; [3+2] cycloaddition